Finding the right spot: where to measure airway parameters in patients with COPD - Gawlitza, Joshua Felix Michael; Haubenreisser, Holger; Henzler, Thomas; Akın, Ibrahim; Schönberg, Stefan; Borggrefe, Martin; Trinkmann, Frederik (European journal of radiology, 2018)
Purpose - The importance of spirometry for management of COPD was reduced in the 2017 revision of the GOLD report. CT derived airway measurements show strong correlations with lung function tests and symptoms. However, these correlations are specific to the airway localization, and currently there is no evidence for the ideal spot. Therefore, the aim of this prospective study was to systematically correlate CT derived airway measurements with extensive lung function testing. - Methods and materials - 65 patients with diagnosed COPD underwent body plethysmography, impulse oscillometry and dose optimized qCT examination (Somatom Force, Healthineers, Germany) in inspiration and expiration. Eight airway parameters (e.g. outer diameter, maximal wall thickness) were acquired for both scans in every lobe for the third to fifth generation bronchus and correlated with the lung function tests. - Results - The most significant correlations between airway parameters were found for the third generation bronchus of the upper left lobe during expiration (25 out of 48 correlation pairs, mean r=-0.39) and for the third generation bronchus of the upper right lobe during inspiration (9 out of 48 correlation pairs, mean r=-0.25). No significant correlations were for example found for the upper right lobe in expiration. - Conclusion - Correlations between airway parameters and lung function tests vary widely between lobes, bronchus generations and breathing states. Our work suggests that the third generation bronchus of the upper left lobe in expiration could be the preferred localization for airway quantification in future studies.
Gesehen am 11.12.2019